THE ANTECEDENTS OF RELATIONAL BENEFITS EXPECTED BY SME’S TO THEIR BANK (A DEMOGRAPHIC FINDING) - Hiqmah, Faizatul (Universitas Brawijaya, Indonesia, 2019)
The purpose of this research is to seek antecedent factors forming benefit expected by SME’s bank customers on having their credit services. The data were collected using questionnaires spread to 150 respondents in three different areas: big city, urban and sub urban. The data were then analyzed using factors analysis to seek factors determining relationship benefit that is expected by SME’s customer and if any determining variables can differentiate benefit expected between SME’s bank customers in big city, urban and rural areas. The limitations of this study are the models are tested only in East Java area banking sectors, with a big city is represented by Surabaya, an urban area is represented by Sidoarjo and Gresik, while sub-urban is represented by Mojokerto, Jombang, Kediri and some areas in Madura. The findings of this research showed that there were different factors determining benefit based on the area. The result of this study provides strategic options for the banking industry to develop their SME’s market share based on areas. The future researcher suggested to explores another factor determines relational benefit by SME’S customer and its bank. Expanding the area of research is also believed to improve the research so it could be more thoroughly.